Women's Spiritual Leadership as a Driver of Visionary Leadership for Sustaining Educational Quality: A Case Study of a Salafi Islamic Boarding School - HM Adibussholeh; Ahmad Khoirul Mustamir; Muslimin Muslimin (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2026)
This study examines how women's spiritual leadership functions as the driving force of visionary leadership in sustaining the quality of Islamic educational institutions within the context of a Salafi Islamic boarding school. While previous studies have separately explored spiritual leadership, visionary leadership, women's leadership, and educational quality, limited attention has been given to the interrelationship among these constructs, particularly in faith-based educational settings. This study employed a qualitative single-case study with an abductive research approach at Pondok Pesantren Al Baqoroh Lirboyo, Kediri, Indonesia. Data were collected through in-depth interviews with Bu Nyai Noer Channah Zamzami Mahrus, family members, teachers, administrators, alumni, and students, complemented by participant observation and document analysis. Data were analyzed iteratively through thematic analysis, integrating empirical findings with relevant theoretical perspectives to enhance analytical rigor and credibility. The findings reveal that women's spiritual leadership serves as the foundation of visionary leadership through four interconnected roles: setting institutional direction, acting as an agent of change, serving as an organizational spokesperson, and developing future leaders through continuous mentoring. These leadership roles collectively strengthen organizational culture, reinforce the institutional identity of Qur'an memorization, and sustain educational quality by internalizing shared spiritual values. The study further demonstrates that women's leadership legitimacy within a patriarchal Salafi environment is primarily derived from spiritual authority, moral integrity, and religious competence rather than formal organizational power. This study extends the literature by integrating Spiritual Leadership Theory and Visionary Leadership Theory into a unified conceptual framework, proposing that spiritual leadership serves as the ethical and motivational foundation of visionary leadership, thereby sustaining educational quality in Islamic educational institutions. The findings also offer a contextual contribution to women's leadership scholarship by demonstrating how spiritual authority enables women to exercise strategic leadership within faith-based organizations.